PENGEMBANGAN POTENSI DESA WISATA PADUKUHAN TAWANGREJO, PURWOBINANGUN, PAKEM, SLEMAN - Prasetyoningsih, Nanik; Iswandi, Kelik; Wardhana, Allan; Mujiyana, Mujiyana; Putra, Ilham; Wrediningsih, Sri (Universitas Muhammadiyah Malang, 2023)
This PKM Community Service Program is being carried out in collaboration with the governments of Padukuhan Tawangrejo, Purwobinangun, Pakem. The UMY PKM team will assist the Tawangrejo Educational Tourism Village Pioneer Team, which has struggled to build and develop the Tawangrejo educational tourism village concept. This Service Program is carried out through a Workshop on Tourism Village Management and Establishment and Field Trips to review the Tawangrejo Area, which will be used as a tourist destination. The workshop was held to improve the Tourism Village Pioneer Team's understanding of managing and establishing a tourist village. The field trip results were then discussed, as was the possibility of structuring the tourist location area and the projection of the establishment of a tourist village, which was then documented in the documentation